Pests and diseases of horticultural crops in Tanjung Seteko Village Indralaya District, Ogan Ilir Regency, South Sumatra - Arsi Arsi; Tika Rahmawati; Amirah Salsabila; Fuji Anugrah; Mira Andani; Fitri Ani; Rintan Sartika Rahmadhonna; Muhammad Arifudin (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Cultivation of horticultural crops is often faced with the problem of plant pests, namely pests and plant diseases which cause plant productivity to decrease. In controlling pests and diseases, farmers often use synthetic pesticides, but farmers use pesticides that do not comply with regulations. The research aimed to identify species of pests and diseases in horticultural crops and farmers' in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency, South Sumatra in controlling pests and diseases of horticultural crops. This research method used purposive sampling and direct observation in the field. The farmers who were interviewed were farmers who grew horticultural crops. The results of this research found that vegetation around plants influences the diversity of pests and diseases. There were 8 pest species found with the highest attack rate of 17.56%, namely Diaphania indica attacks and the lowest attack intensity was Valanga sp. 0.19%. There were 8 types of diseases found with the highest attack rate being 41.11% (Cucumber mosaic virus) and the lowest at 0.56% (fusarium wilt). Pest and disease control with the application of synthetic pesticides by farmers was in a good category. The scoring of farmer’s respondent statements in Tanjung Seteko Village was obtained with a score range of 28-41. The scoring results show that farmer’s behavior in using pesticides is in the good category.